Boosting English Competency and Learning Motivation Through the Integrated Approach For Non-English Departments Students - Samsul Amri; Syafrizal (ELT-Lectura, 2021)
At the tertiary level, English as a General Subject supports the learning process's main course. The observations show they are not yet proficient enough to use it. It causes indisposed motivation, dearth vocabulary, low learning interest, short time allocation, and others. Therefore, the researchers provide a solution by applying the Integrated Approach. The research objectives are to determine whether the Integrated Approach can improve English competency and learning motivation, how the learners’ improvement process, and what factors influence these improvements. It is action research, which was Accounting majoring students as subjects - Islamic University of Indragiri. The data collection process used tests and questionnaires. Furthermore, the results showed an increase in their competence and motivation to learn English before and after the Integrated Approach. The improvement process covers several activities; socializing, analyzing, monitoring, guiding, and practicing. Meanwhile, the development affecting factors are internal and external factors such as learning motivation, teaching methods, and the instructors’ roles. In conclusion, the Integrated Approach application positively contributes to the learners’ learning outcomes and motivation.